Essential oil analysis and antibacterial activity of Ferula assa-foetida L. aerial parts from Neishabour mountains - N. Samadi; S. Shahani; H. Akbarzadeh; S. Mohammadi-Motamed; E. Safaripour; F. Farjadmand; M. Eftekhari; H.R. Monsef-Esfahani; M. Khanavi (Iranian Society of Pharmacognosy, 2016)
Background and objectives: Ferula assa-foetida (asafoetida) is a native Iranian species which grows in different regions and climates in Iran. The plant is well known in Iranian Traditional Medicine as well as folk medicine for treatment of diseases. Several studies have been carried out on the essential oil of this species collected from different areas of Iran. This study is the first report about the essential oil of the plant collected from Neishabour mountains that is a potent area for growing this valuable plant species. Methods: Essential oil of the aerial part of Ferula assa-foetidawhich wascollected from Neishabour, Iran, was analyzed by gas chromatography-mass spectroscopy (GC/MS). The minimum inhibitory concentrations of the essential oil was investigated against both Gram-positive (Staphylococcus epidermidis, Staphylococcus aureus, Bacillus subtilis) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumonia) bacteria using microdilution method. Results: Twenty three components representing 97.06% of the total oil were identified. (E)-1-propenyl sec-butyl disulfide (53.77%), (Z)-1-propenyl sec-butyl disulfide (35.6%) and α-pinene (3.4%) were identified as major components. The MICof the essential oil ranged from 12-24 mg/mL against all tested bacteria. Conclusion: The results indicated that among various compounds identified in the essential oil of F. assa-foetida L. from Neishabour mountains, disulphide compounds were the major constituents of the oil. In comparison to other reports of this plant around the country, disulphide compounds could be the reason of its moderate antibacterial effect.